Menu Close

Question-45495




Question Number 45495 by Meritguide1234 last updated on 13/Oct/18
Answered by tanmay.chaudhury50@gmail.com last updated on 13/Oct/18
Commented by tanmay.chaudhury50@gmail.com last updated on 14/Oct/18
∫_(a−2b) ^(2a−b) ∣(√((x+3b)((2a−b−x)))  −(√((3a−x)(2b−a+x))) ∣dx  ∫_(a−2b) ^(2a−b) (√((3a−3b−x+3b)×(2a−b−(3a−3b−x)))   −(√((3a−x)(2b−a+x))) ∣dx  ∫_(a−2b) ^(2a−b) ∣(√((3a−x)(2b−a−x))) −(√((x+3b)(2a−b−x))) dx  ∫_(a−2b) ^(2a−b) ∣p−q∣dx=∫_(a−2b) ^(2a−b) ∣q−p∣dx  that means p−q=q−p  2p=2q    p=q  (x+3b)(2a−b−x)=(3a−x)(2b−a−x)  2ax−bx−x^2 +6ab−3b^2 −3bx=6ab−3a^2 −3ax−2bx+ax+x^2   2ax+2ax−4bx+2bx−x^2 −x^2 +6ab−6ab=0  4ax−2bx−2x^2 =0  2x(2a−b−x)=0  x=2a−b
a2b2ab(x+3b)((2abx)(3ax)(2ba+x)dxa2b2ab(3a3bx+3b)×(2ab(3a3bx)(3ax)(2ba+x)dxa2b2ab(3ax)(2bax)(x+3b)(2abx)dxa2b2abpqdx=a2b2abqpdxthatmeanspq=qp2p=2qp=q(x+3b)(2abx)=(3ax)(2bax)2axbxx2+6ab3b23bx=6ab3a23ax2bx+ax+x22ax+2ax4bx+2bxx2x2+6ab6ab=04ax2bx2x2=02x(2abx)=0x=2ab

Leave a Reply

Your email address will not be published. Required fields are marked *